Analisis Model Bisnis pada Kelompok Kesenian Tradisional di Kapenewon Kasihan Kabupaten Bantul D.I. Yogyakarta Sebagai Upaya Peningkatan Sense of Entrepreneurship pada Pekerja Seni Analysis of Business Models in Traditional Arts Groups in Kapenewon Kasiha - Akhir Lusono; Wahyu Eko Prasetyanto; Endah Marendah Ratnaningtyas (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
Art workers are one group of workers who are still considered informal workers. In fact, art is a field that should have high value because art can only be produced by high creativity and creative work. Many art activists make art an inferior activity because they think that art cannot be used as the main source of income. This has an impact on the low sense of entrepreneurship of the artists. Not many art workers are willing to build a business in the art industry. The purpose of this research is to analyze the business model that is suitable for artists so that the sense of entrepreneurship possessed by these artists can emerge and improve. The research method used is descriptive qualitative with a literature study approach. The data used are primary and secondary data. The results of the study state that the Canvas business model is one of the business models that is considered very easy to understand so that it is suitable for the characteristics of artistic workers who still have a fairly low sense of entrepreneurship. There are several things that must be considered in designing the Canvas business model, namely Customer Segments, Value Portions, Networks, Relationships with Customers, Revenue Streams, Main Resources, Core Activities, Key Partnerships, and Cost Structures